STUDY ON THE HARDNESS OF OAK WOOD - Mladenova, Diyana (Innovation in Woodworking Industry and Engineering design, 2016)
The hardness is among the most important properties of wood. It is closely correlated with the density and mechanical properties. Moreover, it determines the processing of wood. The scope of the stem varies greatly by determination is often very difficult to define.This work considers the hardness of oak wood, sourced from different habitats in the country and its distribution in the radius of the stem. The influence of age, the width of the annual ring, habitat and altitude are also considered.